2008
DOI: 10.1016/j.bbi.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress exacerbates primary vaginal herpes simplex virus type 1 (HSV-1) infection by impairing both innate and adaptive immune responses

Abstract: Chronic psychological stress is generally immunosuppressive and contributes to an increase in herpes simplex virus (HSV) pathogenicity. We have previously shown that mice experiencing stress at the time of intranasal HSV infection have increased levels of infectious virus in their nasal cavity, as compared to control mice that were not subjected to stress. We have extended our studies to determine the effects of stress at another clinically-relevant mucosal site by examining the immune response to and pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 68 publications
2
21
0
2
Order By: Relevance
“…Prior work has shown that levels of Ach increase during stress (Schlereth et al, 2007), and stressed individuals appear to be more susceptible to a wide range of opportunistic infections (Ashcraft and Bonneau, 2008; Wu et al, 2005). The elements responsible for increasing infection after stress are incompletely understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has shown that levels of Ach increase during stress (Schlereth et al, 2007), and stressed individuals appear to be more susceptible to a wide range of opportunistic infections (Ashcraft and Bonneau, 2008; Wu et al, 2005). The elements responsible for increasing infection after stress are incompletely understood.…”
Section: Resultsmentioning
confidence: 99%
“…Stress mobilizes various elements from the neuroendocrine system to modulate immune responses. Acute stress was typically thought to be immunoenhancing as part of the “fight-or-flight” response, while sustained stress tends to be immunosuppressive (Aberg et al, 2007; Ashcraft and Bonneau, 2008; Dhabhar, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Psychological stress results in the enhanced production of corticosteroids and catecholamines [21] which are potent immunomodulators [22]. In animal models, high-stress environments have been associated with increased morbidity and mortality following bacterial and viral infection [23,24]. People experiencing stressful life events, such as marital problems or caring for a sick relative, have been shown to have altered immunity such as a lower antibody response to influenza vaccination [25] and reactivation of latent viral infections [26].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism through which these stress factors impact HSV disease severity and recurrences is thought to be suppression of the immune system, permitting the viruses to escape immune surveillance (2,7,12,19). However, the receptors for the two major stress hormones, epinephrine and cortisol, are expressed selectively by the different types of neurons infected by HSV, including sensory and autonomic neurons (20,21).…”
mentioning
confidence: 99%
“…Psychosocial stress has been correlated with oral herpes recurrences in humans (8). Psychological stress at the time of infection increases HSV-1 titers and pathology following intranasal or vaginal infection in mice (7,9). Epinephrine (EPI), a catecholaminergic hormone secreted by the adrenal medulla to induce the "short-term" fight-or-flight stress response, is regulated by the sympathetic nervous system.…”
mentioning
confidence: 99%